Use the properties of operations to subtract ( h + k ) - ( 2k + h )

-k

-2h - k

2h + k

2h - k

1 answer

To simplify the expression \((h + k) - (2k + h)\), we can use the properties of operations:

  1. Start with the expression: \[ (h + k) - (2k + h) \]

  2. Distribute the negative sign to the terms inside the parentheses: \[ = h + k - 2k - h \]

  3. Now, combine like terms:

    • The \(h\) and \(-h\) cancel each other out: \[ = (h - h) + (k - 2k) = 0 + (k - 2k) = 0 - k = -k \]

Thus, the simplified result is: \[ -k \]

The correct answer is \(-k\).